Study the thermal impact of massive waste material to building construction - Eusuf, Muhammad Abu; Hasan , Abdullah Al (Trans Tech Publications Ltd., Switzerland, 2013)
This study focuses on the recycling of massive waste materials and their thermal impact to buildings, which then adapt the indoor thermal environment. It is observed that the role of construction materials modify the building interior and consequently regulates the indoor thermal environment and focus on the reduction of energy consumption at large. The rapid growth of energy consumption has raised concerns in worldwide. This has caused mainly the exhaustion of energy resources. Efficient employs of energy play a vital role in minimizing the energy usage. Having in mind the aim to seek for contextual alternative building material from waste to obtain continuing improvement in building energy performance, then this study has been designed to do experiments on locally available massive waste material (end-of-life tires, or ELTs) and investigate its thermal impact on indoor energy management strategy.For that reason, it is needed to set up an experiment to observe the role of ELT for thermal comfort in a tropical climate as compared to conventional construction materials and other waste. This contribution mainly focuses on the literature and a proposed methodology.